Socio-Economic and Health Literacy Inequalities as Determinants of Women’s Knowledge about Their Reproductive System: A Cross-Sectional Study - Viktória Prémusz; Kálmán András Kovács; Eszter Skriba; Zoltán Tándor; Gábor Szmatona; Olívia Dózsa-Juhász (Epidemiologia)
Background/Objectives: To support women’s informed decisions and reproductive self-care, confident reproductive health-related knowledge is needed, supported by adequate health literacy (HL). No corresponding survey has been carried out in Hungary on inequalities to provide information addressing education. Materials and Methods: In the current cross-sectional online survey, 301 women of reproductive age (27.16 ± 0.36 years) were asked with the Hungarian versions of validated and standardised questionnaires about reproductive knowledge on hormones, ovulation, menstrual cycle, pregnancy signs and birth control (Knowledge of Female Body Scale—KFB), and HL (Brief Health Literacy Screening Tool—BRIEF). Spearman correlation and multivariable linear regression analyses were utilised, with a significance level set at p < 0.05. IBM SPSS version 28.0 (IBM SPSS, Armonk, NY, USA: IBM Corp.) and G*Power (version 3.1.9.7; Heinrich-Heine-Universität Düsseldorf, Düsseldorf, Germany) software. The STROBE checklist was followed. The Clinical Trial Registry Nr. is NCT06146673. Results: The KFB composite score was high (20.01 ± 2.33); 86.374% had “high knowledge”. Still, lacking information was identified for the mechanisms of certain contraceptive methods and early physical signs of pregnancy. A significant difference was also found in the KFB scores in the case of higher age (p = 0.019), higher education level (p = 0.018) and previous live birth (p = 0.028). A positive correlation was found between KFB and HL (p < 0.001), education (p = 0.005), and age (p = 0.021). A multiple regression analysis (R2 = 0.087, p < 0.001) indicated that both HL (p < 0.001) and age (p = 0.003) are potential positive predictors of adequate reproductive knowledge, whereas induced abortion (p = 0.013) might serve as an inverse predictor. Conclusions: Inequalities in women’s knowledge about their reproductive system and HL were found, and it was significantly the lowest in their highest conception probability age. Therefore, in addition to targeted education, HL also needs improvement.